GEREJA YANG EKOLOGIS MENGACU RUMAH PANGGUNG DALAM KONTEKS KOTA BANJARMASIN - Lia Afriliani; Lantigimo, Enta Malasinta; Keloso (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2025)
This study analyzes the ecological values embodied in stilt houses and proposes a model of ecological ecclesiology within the context of Banjarmasin City. A qualitative method was employed, using interviews, observations, and literature reviews. The findings reveal that stilt house construction in Banjarmasin reflects harmony between humans and nature, with architectural designs adapted to floods and tidal shifts. These houses also help preserve local wisdom, minimize environmental impact, and strengthen social and spiritual interactions. Such values may serve as a model for the church in carrying out its ecological mission, enabling it to contribute to environmental sustainability while fulfilling its spiritual and social calling.